Beiträge zur Insektenfauna der DDR: Coleoptera - Curculionidae (Apioninae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1977)
The subfamily Aponinae is represented in Central Europe by the genus Apion Herbst only, which in this region includes 44 subgenera and 140 species. In the GDR 110 species are to be found. Each of these 140 species is discussed under the following aspects: host plants, mode of life, general distribution, distribution in Central Europe, and for agricultural pests, economic significance. For the 110 species occurring in the DGR the distribution in the 15 districts is noted. The distribution was established by evaluating the literature and the most important collections and by the author’s excursions, made especially to those districts of the GDR that had not been extensively covered by faunistic studies before. Several species of Apion attack clover, lucerna and vetch.